Ecology and Conservation of the Endangered Indochinese Freshwater Pearl Mussel, Margaritifera Laosensis (Lea, 1863) in the Nam Pe and Nam Long Rivers, Northern Laos. (December 2014) - Bolotov, Ivan; Vikhrev, Ilya; Bespalaya, Yulia; Artamonova, Valentina; Gofarov, Mikhail; Kolosova, Julia; Kondakov, Alexander; Makhrov, Alexander; Frolov, Artyom; Tumpeesuwan, Sakboworn; Lyubas, Artyom; Romanis, Tatyana; et al.
In this paper we present the first ecological data of Indochinese freshwater pearl mussel, Margaritifera laosensis populations. We also provide a comparative study of the ecology of this tropical species with populations of other Margaritiferidae. We conducted surveys in ten tributaries of the River Nam Ou (Middle Mekong Drainage, Northern Laos). Reproductively viable populations were found only in the Nam Long and Nam Pe rivers, which are two of the only three known viable populations of this species in the world. The habitats of M. laosensis include mountainous oligotrophic rivers with circumneutral pH. Optimal mesohabitats are riffles and runs with a median depth of 0.2 m and median current velocity of 0.3 ms −1 . Pearl mussels were more common in gravel and fine gravel riverbed substrates. Surveys revealed 252 specimens, but only 78 (31.0%) were alive. The largest mussels observed were 110 mm in length and only 11–12 years of age. The presence of smaller-sized mussels indicates recent recruitment in both populations. The most significant threats to M. laosensis populations are harvest by local people and land development in the River Nam Ou Basin.